FEA Analysis of S-PMSG for Aircraft Application - Thangaraj, Bharathi; Arumugam, Deepak; Somasundaram, Gomathi (International Journal of Engineering and Technology, 2018)
In this work the performance analysis of Spoke type Permanent Magnet Synchronous Generator (S-PMSG) also called buried type PMSG is presented for aircraft application. The analytical design of the generator is carried out using design equations and it is verified by RMxprt software. The simulation analysis of the generator is performed by finite element analysis software. The coupled transient electromagnetic field and thermal analysis of the generator is carried out to find the load voltage, load current, cogging torque, heat generation and thermal heat flow. Finally, the overall performance of the analytically designed generator is compared with the simulation results.